2013
DOI: 10.1016/j.celrep.2013.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Mitochondrial RNA-Protein Interactions by Digital RNase Footprinting

Abstract: Human mitochondrial DNA is transcribed as long polycistronic transcripts that encompass each strand of the genome and are processed subsequently into mature mRNAs, tRNAs, and rRNAs, necessitating widespread posttranscriptional regulation. Here, we establish methods for massively parallel sequencing and analyses of RNase-accessible regions of human mitochondrial RNA and thereby identify specific regions within mitochondrial transcripts that are bound by proteins. This approach provides a range of insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Matthews to assess the performance of protein secondary structure prediction [12]. Then, it becomes a widely used performance measure in biomedical research [13–17]. MCC and Area Under ROC Curve (AUC) have been chosen as the elective metric in the US FDA-led initiative MAQC-II that aims to reach a consensus on the best practices for development and validation of predictive models for personalized medicine [16].…”
Section: MCC Metric For Imbalanced Datamentioning
confidence: 99%
“…Matthews to assess the performance of protein secondary structure prediction [12]. Then, it becomes a widely used performance measure in biomedical research [13–17]. MCC and Area Under ROC Curve (AUC) have been chosen as the elective metric in the US FDA-led initiative MAQC-II that aims to reach a consensus on the best practices for development and validation of predictive models for personalized medicine [16].…”
Section: MCC Metric For Imbalanced Datamentioning
confidence: 99%
“…Another aspect of mito-nuclear RNA-protein co-evolution is reflected in the need for compatibility between the mtDNA-encoded tRNA Tyr and the nDNA-encoded tRNA Tyr-synthase to maintain normal development and mitochondrial function among Drosophila taxa ( Hoekstra et al, 2013 ; Meiklejohn et al, 2013 ). The recent identification of mitochondrial mRNA-binding by proteins and miRNAs ( Mercer et al, 2011 ; Liu et al, 2013 ; Wolf and Mootha, 2014 ; Zhang et al, 2014 ) may assist in isolating such binding factors and investigating their co-evolution with the bound mtDNA-encoded mRNAs. Such approaches may, in turn, assist in the identification of proteins involved in modes of mtDNA transcript modification, such as the recently discovered human mitochondrial RNA editing ( Bar-Yaacov et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The modular 35-amino-acid sequence repeated in tandem in canonical P motifs is characterized by high affinity for interactions with RNA ( 8 , 9 , 15 ). The binding to RNA is determined by amino acids located in specific positions of each P motif, defining a molecular code which establishes the modality of RNA recognition by PPR proteins ( 17 21 ). Recent structural work has shown that each P motif forms a hairpin of two antiparallel α-helices connected by a short turn of two amino acids ( 20 ).…”
Section: Introductionmentioning
confidence: 99%